SSC-associated magnetic variations at the geosynchronous altitude - Kuwashima, Masayuki; Tsunomura, Satoru; Fukunishi, Hiroshi (1984)
P(論文) SSC events at the geosynchronous altitude have been studied using the data obtained at the geosynchronous satellite, SMS/GOES, as well as the data obtained on the ground for the period from 1976 to 1980. In the compressional component (parallel to the ambient magnetic field direction), the SSC amplitude is very large in the noonside, while it becomes smaller with increasing distance from the noonside and is very small or none in the midnightside. In the transverse component (east-west direction), the direction of the initial movement of Psc changes drastically across the noon and the midnight. The direction is eastward in the morningside, while it is westward in the eveningside. These observational results will be examined quantitatively in the present study. departmental bulletin paper